A Nonlinear Method for Long-term Optimal Operations for Cascade Hydropower Plants with Electricity-Price Curves. Issue 1 (April 2020) - Shen, J J; Zhong, H; Cheng, X
Abstract: Based on the electricity market of Yunnan Province in China, a nonlinear method for long-term optimal operations for cascade hydropower plants with electricity-price curves is developed. This method takes into account multiple trading varieties that include matching, outside, and priority. With a large amount of historical market transaction data, the regression analysis method is used to determine a nonlinear relationship curve between electricity and price of each market variety. Moreover, the differences of the price characteristics in flood season and dry season are also considered. The fitted electricity-price curves are utilized to formulate an optimization model with maximizing generation benefit. The hydropower nonlinearities of this model are handled by the polynomial technique to obtain a solvable MINLP model. The simulation results demonstrate that the proposed method can reasonably determine the declared electricity quantity of cascaded hydropower plants in different trading markets depending on the electricity-price relationships. It is suggested that low-price electricity in flood season should be transferred to high-price electricity market in dry season since the total power generation benefit of the system can be effectively improved.